Dynamic stiffness elements for free vibration analysis of rectangular Mindlin plate assemblies. (22nd December 2015) - Kolarevic, N.; Nefovska-Danilovic, M.; Petronijevic, M.
Abstract: The dynamic stiffness matrix of completely free rectangular Mindlin plate element is presented in this paper. The system of three coupled equations of motion is transformed into two uncoupled equations introducing a boundary layer function. The dynamic stiffness matrix is derived by use of the superposition method and the projection method. Using the proposed method natural frequencies of individual plates and plate assemblies with arbitrary boundary conditions are computed and validated against the results available in the literature and the finite element analysis. High efficiency and accuracy of the results are demonstrated.